A new principle to attenuate ischemia-reperfusion injury in kidney transplantation - Biglarnia, Ali-Reza ; 0009-0004-2293-0740; Teramura, Yuji; Asif, Sana; Dührkop, Claudia; Manivel, Vivek Anand; Manell, Elin; Hedenqvist, Patricia; Rydén, Anneli; Sellberg, Felix; Fromell, Karin; Hammer, Sabine; Huber-Lang, Markus; et al. (American Journal of Transplantation, 2025)
Ischemia-reperfusion injury in transplantation remains a significant clinical challenge with regard to both short-term and long-term complications. In this study, we developed a new amphiphilic construct, polyethylene glycol (PEG)-conjugated lipids (PEG-LIPIDs), to be administered ex vivo intra-arterially to procured porcine kidney allografts before reperfusion. The aim was to create a protective cell membrane barrier, preventing the recognition of ligands exposed on renal cells by plasma proteins and cells of the intravascular innate immune system. In vitro cell studies confirmed the safety of PEG-LIPID with no observed toxicity and demonstrated its efficacy in masking ligands on various cell types. The PEG-LIPID was evaluated in 3 porcine allogeneic transplant models: 1 acute dual en bloc nonsurvival transplant model (duration 6 hours) and 2 survival models with low and high ischemic stress, respectively (duration 96 hours). No immunosuppression was employed. Across all 3 porcine transplant models, PEG-LIPID consistently mitigated ischemia-reperfusion-induced thromboinflammation (complement, coagulation, and kallikrein/kinin activation) and long-term inflammation with a marked reduction in cytokine responses, including lower levels of interleukin 6. The PEG-LIPID-treated kidneys exhibited significantly improved allograft function, reflected in robustly lower creatinine levels. This translational study confirmed that the PIG-LIPID is a strong candidate drug to mitigate ischemia-reperfusion injury in clinical kidney transplantation.
Copyright © 2025 The Author(s). Published by Elsevier Inc. All rights reserved.